Cognitive-Behavioral Therapy for Insomnia Tailored to Patients With Cardiovascular Disease: A Pre–Post Study. Issue 3 (3rd May 2020) - Heenan, Adam; Pipe, Andrew; Lemay, Kyle; Davidson, Judith R.; Tulloch, Heather
ABSTRACT: Objective : There is little research assessing the use of cognitive-behavioral therapy for insomnia (CBT-I) among patients with cardiovascular disease (CVD), even less on the effects of CBT-I on CVD risk factors such as anxiety and depression, and to our knowledge, only limited studies of the efficacy of CBT-I protocols with cardiac disease-specific modifications. The objective of this study is to evaluate a group-based CBT-I intervention tailored to patients with CVD on sleep quality, duration, and mental health. Participants : A sample of 47 participants (25 men) diagnosed with primary insomnia were included in this study. Methods : This study used a pre–post design comparing outcomes before and after a group intervention. Clinicians in a cardiac center referred CVD patients with self-reported sleep disturbance to the intervention group. Following screening and confirmation of insomnia disorder, participants completed a six-week CBT-I group-based intervention tailored for patients with CVD. Participants completed sleep diaries and questionnaires, including the Insomnia Severity Index, Beck Depression Inventory-II, and Beck Anxiety Inventory, pre- and postintervention. Results : Participants' sleep outcomes (sleep duration, maintenance, efficiency, latency, and quality) were significantly improved and patients reported significantly fewer symptoms of anxiety, depression, and insomnia following the CBT-I intervention ( p values < .05). Conclusions : After participating in a CBT-I group intervention tailored for cardiac patients, patients reported improved sleep and significantly lower levels of anxiety and depression. Randomized trials of this intervention are warranted.